Etude et simulation une phasemètre - أحمد, مصباحي; باسين, لجدر علي (Université d'El Oued, 2021)
"Abstract: This thesis presents the most commonly used methods for measuring the phase shift between electrical signals. The traditional methods are described there, in particular those based on the use of an oscilloscope, then a large place is devoted to the methods, appeared more recently, implementing digital techniques. The phase shift measurement between signals embedded in noise is also discussed. The object of our work is the study and simulation of the electrical circuits of an LED display phasemeter " " تقدم هذه الأطروحة الطرق الأكثر استخدامًا لقياس انزياح الطور بين الإشارات الكهربائية. يتم وصف الطرق التقليدية هناك ، ولا سيما تلك القائمة على استخدام الذبذبات ، ثم يتم تخصيص مكان كبير للطرق ، ظهر مؤخرًا ، تنفيذ التقنيات الرقمية. كما تمت مناقشة قياس انزياح الطور بين الإشارات المضمنة في الضوضاء. الهدف من عملنا هو دراسة ومحاكاة الدوائر الكهربائية لجهاز قياس الطور بشاشة ثنائي باعث الضوء "
Systeme de telecommunication مذكرة ماستر تخصص
Keywords: phasemeter; LED; phase shift; simulation ; ISIS; digital; مقياس الطور. اضاءة منخفضة ؛ مرحلة التحول؛ محاكاة ؛ معالج؛ رقمي